Mucosal Schwann cell hamartoma of the gallbladder - Ismael, Farhan; Khawar, Sidrah; Hamza, Ameer Hamza (Autopsy and Case Reports, 2021)
Mucosal Schwann cell hamartoma (MSCH) is a rare benign neurogenic tumor characterized by pure S100p positive spindle cell proliferation. Most cases occur in the distal colon. Involvement of the gall bladder is exceedingly rare. There have been no reports of recurrence or a syndromic association with MSCH. Herein, we describe a case of MSCH of the gallbladder in a 55-year-old female patient with prior history of gastrointestinal neurofibromas who presented with abdominal pain. MR imaging revealed choledocholithiasis, gallbladder thickening, and marked biliary and pancreatic ductal dilation. The patient subsequently underwent cholecystectomy with choledochoduodenostomy. Histologic evaluation of the gallbladder showed diffuse expansion of the mucosa with S100p positive cells with spindly nuclei and indistinct cytoplasmic borders and diagnosis of MSCH of the gallbladder was rendered.